2012
DOI: 10.1111/j.2041-1014.2012.00643.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Porphyromonas gingivalis extracytoplasmic function sigma factor, SigH

Abstract: Summary Little is known about the regulatory mechanisms that allow Porphyromonas gingivalis to survive in the oral cavity. Here we characterize the sigma (σ) factor SigH, one of six extracytoplasmic function (ECF) σ factors encoded in the P. gingivalis genome. Our results indicate that sigH expression is upregulated by exposure to molecular oxygen, suggesting that sigH plays a role in adaptation of P. gingivalis to oxygen. Furthermore, several genes involved in oxidative stress protection, such as sod, trx, tp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 63 publications
(154 reference statements)
1
32
0
Order By: Relevance
“…In both parent and mutant strains Na + depletion lead to significant upregulation of genes previously identified as responsive to oxidative stress in P. gingivalis [22], [23]. As shown in Table 2, these included formate-tetrahydrofolate ligase (PG1321), formate-nitrite transporter (PG0209), thiol peroxidase (PG1729), ferritin (PG1286) and thioredoxin (PG0034).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…In both parent and mutant strains Na + depletion lead to significant upregulation of genes previously identified as responsive to oxidative stress in P. gingivalis [22], [23]. As shown in Table 2, these included formate-tetrahydrofolate ligase (PG1321), formate-nitrite transporter (PG0209), thiol peroxidase (PG1729), ferritin (PG1286) and thioredoxin (PG0034).…”
Section: Resultsmentioning
confidence: 95%
“…2 hr in medium with and without Na + (Table 2). Under Na + -depleted conditions both parent and mutant strains appeared to undergo oxidative stress as evidenced by up-regulation of genes known to be involved in the response [9], [22], [23], [25]. In most cases the relative levels of expression were greater in the rprY mutant than in the parent indicating that the regulator controls expression of genes important for growth and survival under these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The P. gingivalis W83 transcriptome was determined as described previously (61). Reads were aligned to the reference genome using the CLC Genomics Workbench (CLC Bio).…”
Section: Methodsmentioning
confidence: 99%
“…The ECF sigma factors have been reported to be involved in virulence regulation in pathogenic bacteria including Mycobacterium tuberculosis , Staphylococcus aureus , Pseudomonas aeruginosa , and Enterococcus faecalis (Hahn et al ., ; Shaw et al ., ; Llamas et al ., ; Wood & Ohman, ; Le et al ., ). The P. gingivalis W83 genome encodes eight sigma factors, six of which belong to the ECF sigma factor subfamily [PG0162, PG0214, PG0985, PG1318, PG1660, and PG1827 (SigH)] (Nelson et al ., ; Yanamandra et al ., ). Previous studies have demonstrated a role for several of the ECF sigma factors for survival of P. gingivalis in the presence of oxygen, hydrogen peroxide, and thiol‐induced stress (Dou et al ., ; Yanamandra et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…The P. gingivalis W83 genome encodes eight sigma factors, six of which belong to the ECF sigma factor subfamily [PG0162, PG0214, PG0985, PG1318, PG1660, and PG1827 (SigH)] (Nelson et al ., ; Yanamandra et al ., ). Previous studies have demonstrated a role for several of the ECF sigma factors for survival of P. gingivalis in the presence of oxygen, hydrogen peroxide, and thiol‐induced stress (Dou et al ., ; Yanamandra et al ., ). In addition, its function as a positive regulator of hemin uptake and virulence regulation in this bacterium is documented (Yanamandra et al ., ).…”
Section: Introductionmentioning
confidence: 97%